2016
DOI: 10.24275/rmiq/alim759
|View full text |Cite
|
Sign up to set email alerts
|

High-presure homogenization and maltodextrins mixtures to microencapsulate vanilla (Vanilla planifolia) extract through freeze-drying

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These technologies are based on the idea of coating the desired active compound. Encapsulation is a process in which small solid particles, liquid components or gaseous materials are coated or entrapped within another inert shell material, which isolates and protects the core material from environmental factors (Zhu et al, 2012;Enciso-Sáenz et al, 2018;Ocampo-Salinas et al, 2017). In addition, this technique helps to mask the unwanted taste and the odor of the ingredient, helps to prevent the evaporation of the volatile components and helps to prevent the contact of the ingredient with oxygen to avoid their oxidation (Turasan et al, 2015;Fuentes-Ortega et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These technologies are based on the idea of coating the desired active compound. Encapsulation is a process in which small solid particles, liquid components or gaseous materials are coated or entrapped within another inert shell material, which isolates and protects the core material from environmental factors (Zhu et al, 2012;Enciso-Sáenz et al, 2018;Ocampo-Salinas et al, 2017). In addition, this technique helps to mask the unwanted taste and the odor of the ingredient, helps to prevent the evaporation of the volatile components and helps to prevent the contact of the ingredient with oxygen to avoid their oxidation (Turasan et al, 2015;Fuentes-Ortega et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…113 The major limitation of these systems is high cost of homogenizers and large amount of heat generated by friction of the emulsions on the homogenizer surfaces, which needs to be dissipated by cooling of the device during its operation. 113,124 The heat generated during homogenization rules out high energy methods from certain applications such as formulation of nanoemulsions containing thermosensitive compounds including proteins and nucleic acids. 113 Another drawback of high energy nanoemulsification is degradation and fragmentation of high molecular weight compounds (e.g.…”
Section: Nanoemulsion Preparation: High and Low Energy Methodsmentioning
confidence: 99%
“…It is an expensive drying process because it requires the use of a vacuum pump, a large amount of energy expenditure, and 24 to 48 h of incubation time [131]. Ocampo-salinas et al [132] performed encapsulation of condensed vanilla extract using a freeze-drying technique followed by micro-fluidization, employing maltodextrins as wall materials. The research demonstrated the formation of vanilla extract microcapsules via a freeze-drying approach with more than 95% encapsulation efficiency.…”
Section: Freeze Dryingmentioning
confidence: 99%